Organizational values according to physicians and nurses in three Hospital centers of Bogota - Arango Bayer, Gloria Lucía (Acta Bioethica, 2016)
This article presents one of the many objectives of a doctorate thesis, oriented towards identifying and describing the institutional values and principles perceived as predominant by nurses and medical practitioners in three hospitals in Bogota. For this reason, a qualitative study of thegrounded theory sort,was carried out, including 49 in-depth interviews with medical practitioners and registerednurses ofthreehospitalslocated in Bogota: one public, one private and one pertaining to a specialregimen of Colombia’s armed forces and police. The results of the afore mentioned study suggest that five predominant values exist in the hospitals: efficiency, hierarchy, image, quality of care and the individual (be it as a patient or as a client). Recommendations are formulated for profesional development, education, research and hospitals.